Peran Guru PAI Dalam Membentuk Karakter Kejujuran Siswa - Fitriani, Lia; Rahmah, Eka Naelia (Prodi Pendidikan Keagamaan Islam, 2024)
Character education is an integral part of the educational process that aims to shape students into individuals who are not only academically intelligent but also have strong morals and ethics. This study aims to explore the role of Islamic Religious Education (PAI) teachers in shaping the character of honesty in class VIII. This research used a descriptive qualitative approach. The research subjects were the principal, an Islamic Religious Education teacher, and 4 students. Data collection used observation, interviews, and documentation. Data collection techniques were analyzed using data collection, data reduction, data presentation, and conclusion drawing. The results showed that the role of Islamic Religious Education (PAI) teachers in shaping the character of honesty of 8th-grade students at Al-Kamiliyyah Boarding School Junior High School went well. In addition, the use of educational media and facilities is an important communication tool that increases the effectiveness of the teaching and learning process.